1977
DOI: 10.2323/jgam.23.175
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Behavior of Rhodosporidium Toruloides, a Heterobasidiomycetous Yeast

Abstract: Nuclear behavior in the cells of Rhodosporidium toruloides, a heterobasidiomycetous yeast, was followed by microscopic observation. The behavior in the process of both asexual and sexual reproduction of the microorganism was found to agree, in principle, with the description on that of Leucosporidium sp., a heterobasidiomycetous yeast. In the artificially induced sexual differentiation in the cells of mating type a strain by A factor (a sex hormone secreted from the cells of mating type A strain), a complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Mating tube formation from a-mating type cells, which is an early event of the sexual process (2), is induced by a mating hormone, rhodotorucine A (3). Formation and elongation of the mating tubes occur with suppression of bud growth and nuclear duplication, and the cells which form mating tubes are mononucleate (4). Apparently there is a certain critical stage for differentiation of mating tubes in the cell cycle of a-mating type cells before nuclear duplication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mating tube formation from a-mating type cells, which is an early event of the sexual process (2), is induced by a mating hormone, rhodotorucine A (3). Formation and elongation of the mating tubes occur with suppression of bud growth and nuclear duplication, and the cells which form mating tubes are mononucleate (4). Apparently there is a certain critical stage for differentiation of mating tubes in the cell cycle of a-mating type cells before nuclear duplication.…”
mentioning
confidence: 99%
“…An agar piece containing the cell-free culture fluid was placed side-by-side between two pieces of M-919 culture (rhodotorucine A-supplying culture containing 2.5 x 10' cells per ml) on a glass slide, and incubated at 27°C for 3 hr. On the other hand, M-1057 cells were adhered to a cover glass as previously described (4), and the side with the adhered M-1057 cells was placed on the piece containing the cell-free culture fluid of M-919, and then cultivated for 5 hr. During the cultivation, the mating hormone was continuously supplied to the target M-1057 cells through agar from M-919 cells which grew in both sides of the agar piece.…”
mentioning
confidence: 99%
“…When a cells were incubated with rhodotorucine A, the hormone was immediately adsorbed on the cells, followed by the establishment of intracellular information(s) for sexual differentiation within 15 min at 30° (8). After 5-hr incubation with the hormone, occurrence of following four events was clearly detected in a cells : i) Inhibition of bud formation; ii) inhibition of nuclear duplication; iii) formation of mating tube; and (iv) formation of rhodotorucine a in extracellular space (2). In this paper, we describe one trial to determine the sequence of these four events.…”
mentioning
confidence: 99%
“…Our previous papers described the biological and chemical aspects on the induction of sexual differentiation in life cycle of heterobasidiomycetous yeasts (1)(2)(3)(4)(5)(6). For example, two kinds of hormones, rhodotorucine A and a, were essentially required for the transference of asexual cycle to sexual cycle in Rhodosporidium toruloides.…”
mentioning
confidence: 99%
“…After the cell fusion, secondary hypha formation occurs in the plasmogamete cells, and the hypha grows as dikaryotic cells with clamp connections. In the previous papers, we reported that A and a cells produce extracellular dif fusible substances inducing the formation of mating tubes in the opposite matingtyped cells, a and A cells, respectively (3,4). Recently, rhodotorucine A was isolated from the culture fluid of A cells (5,6), and its chemical structure was confirmed to be (H) Tyr-Pro-Glu-Ile-Ser-Trp-Thr-Arg-Asn-Gly-Cys-S-farnesyl ether (in press in B.B.R.C.).…”
mentioning
confidence: 99%